Madrasah-Based Quality Improvement Management (Multi Site Study At Man In Central Tapanuli Regency) - Harahap, Muhammad Rifai; Nasution, Wahyudin Nur; Hadijaya, Yusuf; Mukhlsin, Ahmad (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
The aim of this research is to analyze Madrasah-Based Quality Improvement Management (Multi- Site Study at MAN in Central Tapanuli Regency). This research uses a multi-site qualitative method where data collection techniques use interviews, observation and document study techniques. Meanwhile, to strengthen the validity of the data findings and the authenticity of the research, the researcher refers to the use of data validity standards suggested by Lincoln & Guba, which consist of credibility, transferability, dependability and confirmability. The results of this research are: 1). Planning to improve the quality of education is carried out by involving all madrasa components and stakeholders. At MAN 1, MAN 2 and MAN 3 Central Tapanuli, the three institutions have planned a program to improve the quality of education by involving stakeholders through 6 steps, namely: (1) making a situation analysis and conditions using SWOT analysis, (2) planning the creation of the madrasah vision and mission, (3) planning the development of the madrasah curriculum, (4) planning the development of teacher competency, (5) planning the provision of infrastructure, (6) planning the development of students to achieve academic achievement and non-academic. 2). Based on the results of cross-case analysis regarding the implementation of improving the quality of education at MAN 1, MAN 2 and MAN 3 Central Tapanuli. Implementation of the education quality improvement program through several activity programs, namely: (1) based on the madrasah vision and mission, (2) increasing teacher competency, (3) ) curriculum development, (4) educational infrastructure, (5) development of student achievement, (6) control is carried out through monitoring and evaluation of work. 3). Evaluating MBM in the Implementation of Education Quality at MAN Central Tapanuli, which is carried out transparently and objectively, is absolutely necessary, and evaluation is the final activity of the management process and actions. It can be concluded that the evaluation at MAN Tapanuli Tengah, evaluation or assessment activities of teachers are usually more focused on individual teacher achievements, especially in the teaching and learning process activities, and their participation in educational activities at madrasas. Apart from the evaluation carried out by the head of the madrasah, supervision is also needed, namely by having a reward system for individual madrasahs, improving the competitive climate between madrasahs, improving the existing system as a whole, and helping madrasahs develop themselves. And 4). The inhibiting factor in implementing MBM in madrasahs is that the role of the madrasah committee is still lacking in becoming a working partner for the madrasah head in making every decision by the madrasah head, which is a joint decision of the madrasah head and madrasah residents so that in implementing these decisions all madrasah residents have a high level of responsibility and commitment.